Pengenalan Pendidikan Literasi Keuangan Bagi Anak Usia Dini Pada Kelas Binaan Jurusan Akuntansi Di Buper - Meinarni Asnawi; Cornelia Desiana Matani; Kurniawan Patma (UNIVERSITAS CENDERAWASIH, 2019)
This community service aims to introduce financial literacy programs for early childhood. Literacy education is important for early childhood so that they are accustomed to financial management well in the future. In Indonesia financial literacy education is still something that is very rarely done, both in the family and school circles, the provision of education about financial literacy has not been done seriously and planned. Service is expected to benefit the knowledge of simple financial management for early childhood through the